Obstructive sleep apnoea and frequency of occupational injury. Issue 7 (15th March 2016) - Hirsch Allen, A J; Park, Julie E; Daniele, Patrick R; Fleetham, John; Ryan, C Frank; Ayas, Najib T
Abstract : Abstract: We sought to determine whether patients with obstructive sleep apnoea (OSA) are at increased risk of occupational injury (OI). Patients referred to the University of British Columbia Hospital Sleep Laboratory for suspected OSA (May 2003 to July 2011 were recruited and rates and types of validated OI (that caused at least 1 day of disability) in the 5 years prior to polysomnography were calculated. In a sample of 1236, patients with OSA were twice as likely (OR=1.93, 95% CI 1.06 to 3.50, p=0.03) to suffer at least one OI compared with patients without OSA. This association was attenuated (OR=1.76, CI 0.86 to 3.59, p=0.12) after controlling for confounders. In a secondary analysis, patients with OSA were almost three times more likely (OR=2.88, CI 1.02 to 8.08, p=0.05) to suffer from an injury more likely related to reduced vigilance (eg, a fall or commercial motor vehicle crash) when compared with patients without OSA, and this again was attenuated after controlling for confounders (OR=2.42, CI 0.085 to 6.93, p=0.10).